2012
DOI: 10.1111/j.1872-034x.2012.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A, B, C and E virus markers in Chinese residing in Tokyo, Japan

Abstract: Indigenous Japanese subjects have less immunity against HAV and HBV. The HBV carrier rate is higher in Chinese subjects, and attention should be paid to this issue in clinical practice. It might be important to control hepatitis viruses in Chinese subjects when doctors see them in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…The reasons for the varying rates of seropositivity are that these surveys were conducted in different regions, on different study populations and using diagnostic reagents of different sensitivities. In the current study, the result is similar to the prevalence of anti-HEV (21%) reported in a study of hepatitis E virus markers in Chinese people residing in Tokyo, Japan [37]. However, it is higher than the seropositive rate of 17.2% which was estimated in the Second National Viral Hepatitis Prevalence Survey in China in 1992 [32].…”
Section: Discussionsupporting
confidence: 88%
“…The reasons for the varying rates of seropositivity are that these surveys were conducted in different regions, on different study populations and using diagnostic reagents of different sensitivities. In the current study, the result is similar to the prevalence of anti-HEV (21%) reported in a study of hepatitis E virus markers in Chinese people residing in Tokyo, Japan [37]. However, it is higher than the seropositive rate of 17.2% which was estimated in the Second National Viral Hepatitis Prevalence Survey in China in 1992 [32].…”
Section: Discussionsupporting
confidence: 88%
“…It is known that HBV vaccine could induce anti-HBs in a majority of vaccinees [ 24 ]. Because there are no universal vaccination programs against HBV in Japan, HBV infections are still viewed as an important issue [ 25 ]. Then, we should consider recipients with anti-HBs as having experienced HBV infection, perhaps a setting different from other countries where universal vaccination programs against HBV exist.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen studies reported the prevalence of HCV infection in high-risk populations: ten were from China [17][18][19][20][21][22][23][24][25][26], two from Japan [27,28], two from Korea [29,30] and five from Taiwan [12,[31][32][33][34]. Among high-risk populations, the prevalence of HCV infection was higher among IDUs (48-95 % in China, Table 4).…”
Section: Prevalence Of Hcv Infection In High-risk Populationsmentioning
confidence: 96%